Conocimientos y prácticas sobre prevención y manejo de enfermedad diarreica aguda, en madres de niños/as del Centro Infantil del Buen Vivir José Miguel Carrión Mora Mies, Loja 2014-2015 - Cabrera Torres, Dayana Esperanza (2015)
The title of the thesis intitulated “Knowledge and Practice about Prevention and Management of acute diarrheal disease in mothers of children of the Centro Infantil del Buen Vivir José Miguel Carrión Mora MIES, Loja, 2014 – 2015” have as objective to determine the knowledge and maternal practices about prevention and management of acute diarrhea in children under 5 years old that attend to the Centro Infantil del Buen Vivir. The research is a descriptive one; the universe was conformed of 92 mothers of children who attend to the CIVB. The techniques used for gathering information were a survey, and as an instrument, an inquiry of questions, the results were: about the knowledge about a greater percentage of mothers know the correct definition of diarrhea, how to prepare oral rehydration salts and oral homemade sera, but a large percentage of them do not know the risk factors, factors protectors, acute diarrheal disease symptoms, signs of dehydration and warning signs to prevent complications, regarding practices was obtained that most participants have adequate practices: about extra alimentation routines, measures for safe water consumption, elimination of waste and sewage, exclusive breastfeeding, cleaning of the bottle, liquid type and time to provide it during diarrhea and continued breastfeeding during diarrhea; while that there are inadequate practices about the presence of intradomiciliary animals, hand washing, care of the food before its preparation, continuity of daily food during the diarrhea. Key Words: Acute diarrheal disease, knowledge, practices, prevention.